Assessing the potential of application of titanium dioxide for photocatalytic degradation of deposited soot on asphalt pavement surfaces. (3rd October 2022) - Reza Omranian, Seyed; Geluykens, Michiel; Van Hal, Myrthe; Hasheminejad, Navid; Rocha Segundo, Iran; Pipintakos, Georgios; Denys, Siegfried; Tytgat, Tom; Fraga Freitas, Elisabete; Carneiro, Joaquim; Verbruggen, Sammy; Vuye, Cedric
Graphical abstract: Highlights: TiO2 exhibited a superb potential to degrade soot and diminish environmental concerns. The response surface method and image analysis techniques exhibited great capabilities to detect and quantify soot degradation. CLSM was found to be an accurate tool to evaluate the distribution of materials (in this study TiO2 ) on specimens. TiO2 may neither negatively nor positively influence the viscoelastic behavior of bitumen. No considerable influence of TiO2 and UV light exposure on the aging indicators (ISO and ICO) was observed. Abstract: It is known that pollutants and their irreparable influence can considerably jeopardize the environment and human health. Such disastrous, growing, hazardous particles urged researchers to find effective ways and diminish their destructive impacts and preserve our planet. This study evaluates the potential of incorporating Titanium Dioxide (TiO2 ) semiconductor nanoparticles on asphalt pavements to degrade pollutants without compromising bitumen performance. Accordingly, the Response Surface Method (RSM) was employed to develop an experimental matrix based on the central composite design. Image Analysis (IA) was used to determine the rate of soot degradation (as pollutant representative) using MATLAB and ImageJ software. Confocal Laser Scanning Microscopy (CLSM), Fourier Transform Infrared spectroscopy (FTIR), and Dynamic Shear Rheometer (DSR) were finally carried out to estimate the effects of adding different percentages of TiO2 on the microstructural features and dispersion of the TiO2, chemical fingerprinting, and rheological performance of the bituminous binder. The results showed a promising potential of TiO2 to degrade soot (over 50%) during the conducted experiments. In addition, the RSM outcomes showed that applying a higher amount of TiO2 is more efficient for pollutant degradation. Finally, no negative impact was observed, neither on the rheological behavior nor on the aging susceptibility of the bitumen, even though the homogenous dispersion of the TiO2 was clearly captured via CLSM.